Superior Character as the Key to Students' Academic Success in the 5.0 Era - Antonio, Lucky; Pujiwati, Pujiwati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to identify the influence of character education on student learning achievement in the context of the 5.0 era. The type of research used is quantitative research. This method was chosen because it is appropriate for testing the relationship and influence between the variables that have been formulated, namely character education and student learning achievement. The research design used is explanatory research. The focus of this study is on three dimensions of character: discipline, self-confidence, and independence. The research subjects consisted of 80 grade XII science students at Mahanaim Middle School in the even semester of the 2022/2023 academic year. The selection of subjects was carried out purposively, considering that the class had received systematic character education intervention through learning tools used at the school. Data collection was carried out through two techniques, namely questionnaires and documentation. The measurement scale used was a four-point Likert scale, with alternative answers ranging from strongly disagree (1) to strongly agree (4), as stated by Riduwan (2004). In addition, documentation was used to obtain quantitative data on student learning achievement, which was taken from the Final Semester Examination (UAS) scores. The results of the study indicate a significant influence, both simultaneously and partially, of discipline, self-confidence, and independence on student achievement. These findings underscore the importance of character education as a primary foundation for improving the quality of learning and student competitiveness in the 5.0 era, where intellectual intelligence needs to be supported by emotional intelligence and strong character. Therefore, schools and educators are expected to continue strengthening the integration of character education into the learning process as a key strategy in producing a superior and globally competitive generation.